2002
DOI: 10.3201/eid0805.010235
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal Carriage ofStreptococcus pneumoniaein Healthy Children: Implications for the Use of Heptavalent Pnemococcal Conjugate Vaccine

Abstract: We assessed the prevalence of Streptococcus pneumoniae serotypes in the nasopharynx of healthy children, antimicrobial susceptibility patterns, risk factors for carriage, and the coverage of heptavalent pneumococcal conjugate vaccine. In 2,799 healthy infants and children, the S. pneumoniae carrier rate was 8.6% (serotypes 3, 19F, 23F, 19A, 6B, and 14 were most common). Most pneumococci (69.4%) were resistant to one or more antimicrobial classes. The rate of penicillin resistance was low (9.1%); macrolide resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
38
4
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 29 publications
11
38
4
4
Order By: Relevance
“…Thus, the response to the primary dose of conjugate in this age group looks more like a naïve response than that seen in adults, even though the vaccine is conjugated. The absence of naturally acquired, polysaccharide-specific IgG B-cell memory in the toddlers prior to immunization might be related to a lack of priming via the nasopharyngeal carriage of pneumococci, except that a number of epidemiological studies have clearly shown that 80% of toddlers have carried the vaccine or vaccine-related serotypes of pneumococci by 1 year of age (10,36,40,61,65). These observations suggest that the amount of pneumococcal carriage experienced during the first year of life may not be sufficient to maintain the levels of IgG or the elevated frequencies of IgG memory B cells against all serotypes in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the response to the primary dose of conjugate in this age group looks more like a naïve response than that seen in adults, even though the vaccine is conjugated. The absence of naturally acquired, polysaccharide-specific IgG B-cell memory in the toddlers prior to immunization might be related to a lack of priming via the nasopharyngeal carriage of pneumococci, except that a number of epidemiological studies have clearly shown that 80% of toddlers have carried the vaccine or vaccine-related serotypes of pneumococci by 1 year of age (10,36,40,61,65). These observations suggest that the amount of pneumococcal carriage experienced during the first year of life may not be sufficient to maintain the levels of IgG or the elevated frequencies of IgG memory B cells against all serotypes in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…Na Europa, estes índices são mais elevados, podendo ser superiores a 50% para os macrolídeos e superiores a 80% para a tetraciclina 27,28 . Estas diferenças podem decorrer dos hábitos de prescrição médica, da quantidade de antibiótico consumida, bem como das diferenças nos genes de resistência bacteriana de uma região para outra 28 .…”
Section: Tabela 3 -Perfil Da Multirresistência De Nove Amostras De Stunclassified
“…Community-based studies of colonization in the United States over the past decade have revealed varying rates of S pneumoniae colonization, 10 -14 with even more extreme international variability reported. 15,16 Resistance profiles differ as well, with some regions reporting less resistance to penicillin but high rates of resistance to macrolides and other agents. 15 Recently published studies from Wisconsin and Utah showed substantial fractions of S pneumoniae with reduced susceptibility to penicillin, but in these rural communities, only 2% to 4% were fully resistant to penicillin (minimum inhibitory concentration [MIC] Ն2.0).…”
mentioning
confidence: 99%
“…15,16 Resistance profiles differ as well, with some regions reporting less resistance to penicillin but high rates of resistance to macrolides and other agents. 15 Recently published studies from Wisconsin and Utah showed substantial fractions of S pneumoniae with reduced susceptibility to penicillin, but in these rural communities, only 2% to 4% were fully resistant to penicillin (minimum inhibitory concentration [MIC] Ն2.0). 17,18 Many of these surveillance studies have been based in child care centers, [12][13][14] where particular strains may be circulating, 19 thus limiting the generalizability of findings to the entire community.…”
mentioning
confidence: 99%